SUPERVISI PENDIDIKAN DALAM MEMBANGUN REPUTASI DAN PENINGKATKAN MUTU PENDIDIKAN - Aprilianti, Yuni; Sudadi, Sudadi; Muadin, Akhmad; Eka Mahmud, Muhammad (An-Nadzir : Jurnal Manajemen Pendidikan Islam, 2023)
Educational supervision is the main element in building the reputation and quality of education. This research aims to investigate whether educational supervision can serve as a vital instrument in maintaining accountability, enhancing the quality of learning, and preserving the reputation of educational institutions. This research employs a library research methodology. The findings of this study reveal the significant role of supervision in an educational context and outline several benefits it yields. Through the effective supervisory process, schools and educators can identify and address weaknesses in teaching methods, curriculum, and assessment. It not only improves the quality of education but also ensures compliance with national standards. Furthermore, educational supervision helps maintain a positive image of schools and educators, enhances customer satisfaction (students and parents), and makes a substantial contribution to building a strong reputation for education. Thus, educational supervision functions not only as a surveillance instrument but also as the key pillar in creating an outstanding and respected education system.